Motivation And Job Satisfaction In Employees - Krishernawan, Indra; Yudiani, Ema; Saiyed, Rahma; Manda, Darmawati; Yanto Rukmana, Arief (Yayasan Pendidikan Belajar Berdikari, 2023)
Important components of the industrial workplace include work motivation, job satisfaction, interpersonal relationships, and non-financial rewards. The purpose of this study is to look into how various motivational factors affect leaders' and employees' communication and cooperation, as well as how non-financial incentives and interpersonal relationships affect workers' job satisfaction and work motivation in the electronics manufacturing sector. Purposive sampling was used in the study to select 91 respondents who worked for Indonesian companies that manufactured electronics. Structural Equation Modelling (SEM) was used to analyse the data that was gathered, and the SmartPLS 3.0 analysis tool was helpful in this process. The findings indicate that employee work motivation is significantly impacted by non-financial incentives. In other words, offering non-monetary rewards by top business executives raises worker motivation. The study's results also demonstrate that interpersonal relationships have no appreciable impact on workers' motivation for their jobs. This indicates that employees' levels of motivation at work are not directly influenced by the interpersonal relationships that exist between them and their bosses. Additionally, the study discovered that employee job satisfaction is significantly impacted by work motivation.